Women’s Economic Abuse Experiences: Results from the UN Multi-Country Study on Men and Violence in Asia and the Pacific - Postmus, Judy L. (Journal of interpersonal violence, 2022)
Economic abuse is a poorly understood form of intimate partner violence but may have far-reaching implications for the financial health of the survivor. Additionally, very little is known about whether depressive symptoms, education, employment, or attitudes about relations between men and women mediate or moderate the relationship between economic abuse and their financial circumstances. The purpose of this study was to answer these two research questions: (a) Is there a relationship between the experience of economic abuse and food insecurity (as a measure of poverty)? (b) Is the relationship between economic abuse and food insecurity impacted by women?s education, women?s and men?s employment, women?s attitudes towards gender relations, or women?s depressive symptoms? We used quantitative data from the ?UN Multi-Country Study on Men and Violence,? analyzing data on 3,105 women aged 18?49 years who were interviewed. Initial logistic regressions were conducted followed by introducing moderators and mediators to the model using path analyses to test the relationship between economic abuse and food insecurity in the household. Significant predictors of food insecurity included several types of abuse and partners? employment, women?s own employment, and education. The only type of IPV not associated with food insecurity was physical abuse. Experiences of economic abuse were associated with a 1.69 times greater likelihood of reporting food insecurity which was higher than experiences of psychological or sexual abuse. Additionally, women?s experiences of economic abuse over their lifetime were significantly associated with an increase in depressive symptoms which in turn was associated with greater likelihood of experiencing food insecurity. Such relationships warrant attention to economic abuse and depressive symptoms as part of the interventions used when working with survivors. Additional research could also help further our understanding of how these variables interact together and how best to address its impact on survivors.